Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/1357633x211041517
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining allied health telehealth services beyond the rapid response to COVID-19: Learning from patient and staff experiences at a large quaternary hospital

Abstract: The patient, clinician and administration staff perspectives of telehealth (specifically videoconferencing) services provided by Allied Health Professions (AHP) at a large quaternary hospital were explored. The purpose was to understand stakeholders’ perceptions of the service during initial COVID-19 restrictions and examine factors that influenced the implementation and sustained use of telehealth. A sequential mixed-methods approach was undertaken. Stage 1 involved surveys completed by patients (n = 109) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 27 publications
8
38
1
Order By: Relevance
“…The necessity for a well-established framework for remote consultations with easy-to-use administrative systems, clear guidelines and centralized technological support was noted by the clinicians in the interviews. These findings align with conclusions from other studies that indicate the necessity of a strategic approach and the involvement of all main stakeholders in the development of telemedicine services [ 36 , 37 ]. Remote consultations must be considered a separate health care service, not an on-site consultation performed remotely, and must be planned and organized accordingly.…”
Section: Discussionsupporting
confidence: 91%
“…The necessity for a well-established framework for remote consultations with easy-to-use administrative systems, clear guidelines and centralized technological support was noted by the clinicians in the interviews. These findings align with conclusions from other studies that indicate the necessity of a strategic approach and the involvement of all main stakeholders in the development of telemedicine services [ 36 , 37 ]. Remote consultations must be considered a separate health care service, not an on-site consultation performed remotely, and must be planned and organized accordingly.…”
Section: Discussionsupporting
confidence: 91%
“…Because almost half the participants indicated they would continue to use telehealth, a review of embedment 12 months after easing of restrictions could allow reflection on the place of telehealth in allied health care beyond crisis management. Our findings also add to a body of literature suggesting that further training to translate traditional practice into a hands-free environment would be positively received (Smith et al 2020;Thomas et al 2020b;Cottrell et al 2021). Including disciplinespecific challenges within this training is also recommended (Krahe et al 2021).…”
Section: Future Recommendationssupporting
confidence: 56%
“…Participants also reported that telehealth adaptation was affected by patients' access to and ability to use the technology. A lack of appropriate equipment, poor Internet connectivity and low digital literacy were frequently raised concerns, and are findings corroborated by Cottrell et al (2021), The Australian Digital Literacy Index (Thomas et al 2020a) and a recent Royal Australasian College of Physicians Australia members survey (Royal Australasian College of Physicians 2020). Several participants also reported that some patients were unwilling to trial telehealth or did not like it, and so disengaged.…”
Section: Discussionmentioning
confidence: 90%
“…In papers which examined SLP experiences with telepractice during COVID, it has been highlighted that some services simply did not have the infrastructure to support telepractice [ 6 , 7 , 13 ]. In addition, many clinicians were unaware of the current evidence for telepractice delivery of dysphagia care, there was a recognized lack of prior training or experience in delivering services via telepractice, a lack of knowledge regarding how to adequately prepare clients for telepractice sessions and manage key issues such as data safety and security, and some faced challenges created by limited reimbursement options [ 6 13 , 16 18 ]. There was equally a critical absence of general knowledge among allied health professionals about how to operate a telepractice service [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many clinicians were unaware of the current evidence for telepractice delivery of dysphagia care, there was a recognized lack of prior training or experience in delivering services via telepractice, a lack of knowledge regarding how to adequately prepare clients for telepractice sessions and manage key issues such as data safety and security, and some faced challenges created by limited reimbursement options [ 6 13 , 16 18 ]. There was equally a critical absence of general knowledge among allied health professionals about how to operate a telepractice service [ 16 , 18 ]. Hence, it was a time of great confusion and anxiety for services, clinical staff, and clients.…”
Section: Introductionmentioning
confidence: 99%